Dialektika Konflik Remaja yang Hamil di Luar Nikah - Gusti Ayu Baby Ananda Putri Astari; Tutut Chusniyah; Indah Yasminum Suhanti (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2020)
This study has a goal to find out how dialectics experienced adolescent with premarital pregnancy. This study uses a qualitative approach. This research model using descriptive qualitative research type. In conducting research, data collection tools that already exist in qualitative methods are semi structured interviews while checking the validity of the findings using member check techniques. The results showed that all participants experienced a process of thinking that was not easy to determine the attitude they should do and the greatest process exists in the adolescent itself, where the teenager experiences a conflict within himself before deciding to take a decision. Adolescents perform a dialectical process in themselves that is related to social relationships such as parents, friends, and couple.